Estimating the impact of better management of glycaemic control in adults with Type 1 and Type 2 diabetes on the number of clinical complications and the associated financial benefit. Issue 11 (15th April 2016) - Baxter, M.; Hudson, R.; Mahon, J.; Bartlett, C.; Samyshkin, Y.; Alexiou, D.; Hex, N.
Abstract: Aim: To estimate potential cost avoidance through modest and achievable improvements in glycaemic control in adults with Type 1 or Type 2 diabetes mellitus in the UK healthcare system. Methods: The IMS Core Diabetes Model was used to examine the impact of improved glycaemic control (indicated by reduction in HbA1c level), in a representative cohort of adults with Type 1 or Type 2 diabetes. The cumulative incidence of microvascular and macrovascular complications was modelled across 5‐year periods to a 25‐year time horizon. Complication costs were applied to the data to estimate potential accrued cost avoidance. Results: Significant cost avoidance of £340 m is apparent in the first 5 years, increasing to £5.5bn after 25 years of sustained improvement in control. The overwhelming majority of cost avoidance arises from reductions in microvascular complications. In people with Type 1 diabetes the greatest cost avoidance comes from a reduction in renal disease (74% of cost avoidance), while in people with Type 2 diabetes it is generated by a reduction in foot ulcers, amputations and neuropathy: 57% cost avoidance). Greater cost reduction is accrued more rapidly in people with higher starting HbA1c levels. Conclusion: Modest improvements in glycaemic control generate significant reductions in the incidence and, therefore, cost of microvascular complications in people with Type 1 or Type 2 diabetes. This study provides clear support for the premise that prioritized and sustained investment in early and better intervention can provide concrete financial benefits in both the short and longer term. What's new?: This study provides estimates of the potential costs avoided as a consequence of reducing the incidence of complications by improving glycaemic control in the current UK adult population with diabetes. By implementing modest and achievable reductions in HbA1c levels, a significant cost avoidance of ˜£340 m is apparent after 5 years. This increases to ˜£5.5bn after 25 years of sustained improvement in glycaemic control. These results suggest that action taken now could produce demonstrable clinical and financial benefit within the next 5 years; sustained intervention will ensure this accrues for decades to come.